Ubiquitous Computing and Computing Security of IoT - Jeyanthi, N.; Abraham, Ajith; Mcheick, Hamid; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This provides a comprehensive overview of the key principles of security concerns surrounding the upcoming Internet of Things (IoT), and introduces readers to the protocols adopted in the IoT. It also analyses the vulnerabilities, attacks and defense mechanisms, highlighting the security issues in the context of big data. Lastly, trust management approaches and ubiquitous learning applications are examined in detail. As such, the book sets the stage for developing and securing IoT applications both today and in the future.
Security Protocols for IoT -- Security in Ubiquitous Computing Environment: Vulnerabilities, Attacks and Defences -- Security of Big Data in Internet of Things -- Trust Management Approaches in Mobile Adhoc Networks -- IoT for Ubiquitous Learning Applications: Current Trends and Future.
Keywords: Computational intelligence; Data protection; Big data; Artificial intelligence; Computational Intelligence; Data and Information Security; Big Data; Artificial Intelligence